Serum Amyloid A is a biomarker of severe Coronavirus Disease and poor prognosis. Issue 6 (June 2020) - Li, Huan; Xiang, Xiaochen; Ren, Hongwei; Xu, Lingli; Zhao, Lisha; Chen, Xiaoqiong; Long, Hui; Wang, Qiang; Wu, Qingming
Highlights: The level of SAA and CRP significantly increased in patients with COVID-19. As disease progressed from mild to critically severe, SAA and CRP gradually increased. Our study indicated that SAA/L, CRP, SAA, and l are valuable in predicting the severity and distinguishing critically ill patients from mild ones. Patients with higher initial SAA are more likely to have poor CT imaging. Summary: Background: To explore the significance of SAA in evaluating the severity and prognosis of COVID-19. Methods: A total of 132 patients with confirmed COVID-19 who were admitted to a designated COVID-19 hospital in Wuhan, China from January 18, 2020 to February 26, 2020 were collected. The dynamic changes of blood SAA, CRP, PCT, WBC, Lymphocyte (L), PLT, CT imaging, and disease progression were studied. All patients completed at least twice laboratory data collection and clinical condition assessment at three time points indicated for this study; The length of hospital stay was longer than 14 days prior to February 26, 2020. Results: COVID-19 patients had significantly increased SAA and CRP levels, while L count decreased, and PCT, WBC, and PLT were in the normal range. As disease progressed from mild to critically severe, SAA and CRP gradually increased, while L decreased, and PLT, WBC, and PCT had no significant changes; ROC curve analysis suggests that SAA/L, CRP, SAA, and L count are valuable in evaluating the severity of COVID-19 and distinguishing critically ill patients from mild ones; Patients with SAA consistently trending down during the course of disease have better prognosis, compared with the patients with SAA continuously rising; The initial SAA level is positively correlated with the dynamic changes of the serial CT scans. Patient with higher initial SAA level are more likely to have poor CT imaging. Conclusions: SAA and L are sensitive indicators in evaluating the severity and prognosis of COVID-19. Monitoring dynamic changes of SAA, combined with CT imaging could be valuable in diagnosis and treatment of COVID-19.